GPR37 Signaling Modulates Migration of Olfactory Ensheathing Cells and Gonadotropin Releasing Hormone Cells in Mice - Saadi, Hassan; Shan, Yufei; Marazziti, Daniela; Wray, Susan (Frontiers in Cellular Neuroscience, 2019)
Gonadotropin releasing hormone (GnRH) neurons, part of the hypothalamic-pituitary-gonadal axis, regulate reproduction. Prenatally, GnRH neurons migrate into the brain from the nasal placode along terminal nerve fibers, intermixed with olfactory sensory axons and olfactory ensheathing cells (OECs). An expression analysis from embryonic GnRH neurons identified the G protein-coupled receptor 37 (GPR37 or PAEL-r). GPR37 has been linked to 1) juvenile Parkinson’s disease in humans, 2) oligodendrocyte differentiation, and 3) Wnt/β-catenin signaling during neurogenesis. In this study, the role of GPR37 was investigated in the developing GnRH/olfactory system. PCR and immunocytochemistry confirmed expression of GPR37 in migrating GnRH neurons as well as in OECs. Inhibition of GPR37 signaling in nasal explants attenuated GnRH neuronal migration and OEC movement. Examination of GPR37 deficient mice revealed a decrease in the olfactory bulb nerve layer and attenuated/delayed maturation and migration of GnRH neurons into the brain. These data demonstrate a developmental role for GPR37 signaling in neural migration.